Massive Gastrointestinal Bleeding Related to NSAID Use in a Patient with Ileorectal Anastomosis - Esere Nesiama; Letisha Mirembe; Kierra Weber; Sruthy Isaac; Deborah Trammell; Izi Obokhare (Case Reports in Surgery)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to reduce pain and inflammation in over 30 million individuals daily. Gastrointestinal bleeding (GIB) associated with NSAID consumption has been well documented in gastric and duodenal bleeding; however, NSAID-associated GIB distal to the duodenum lacks extensive documentation. This report highlights small bowel occult bleeding related to NSAID use in a patient with a surgical history of robotic total colectomy with ileorectal anastomosis completed 1 year prior. In the case of bright red blood per rectum with associated NSAID use, we recommend NSAID cessation followed by an individualized treatment plan, such as upper/lower endoscopy and/or angioembolization.